Determinants of Depression among Diabetes Mellitus Patients in Indonesia: a Cross-sectional Study - Rosalia Putri; Marthoenis Marthoenis; Said Usman; Irwan Saputra; Nurjannah Nurjannah (Budapest International Research in Exact Sciences (BirEx) Journal, 2022)
Depression is a chronic disease among people around the world and seriously global health threat. People with diabetes are 2 to 3 times more likely to experience depression, someone who is depressed will be at bad risk during the treatment process so that it can increase the risk of morbidity and mortality prevalence. Depression can make a person pay less attention to self-care such as not complying with medication instructions, and at high risk for macrovascular and microvascular complications. This study aims to identify the determinants of depression among patients with diabetes mellitus. The method from this research is a cross-sectional approach using a convenience sampling technique with a sample size of 137 respondents. The research results is the prevalence of depression was 8.8%. Southeast Asia is the first ranks with the largest people with depression sufferers reach 27% compared to the West Pacific Region 21%. There was significant correlation between complications and depression in patients with diabetes mellitus (P <.001). However, there was no significant relationship between age (P = .749) employment status (P = .179), gender (P = .082), level of knowledge (P = .968), utilization of health facilities (P = .504, medication adherence (P = .249), level HbA1c (P = .908), and body mass index (P = .573). The results of the multivariable linear regression test showed that complications affected depression (P = .002, r = .300, R2 = .090). The conclusion for this study, Complications are one of the determinants of depression in people with diabetes mellitus in the City of Banda Aceh and Aceh Besar.